2019
DOI: 10.1111/his.13853
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary variant of mucinous carcinoma of the breast shows genetic alterations intermediate between those of mucinous carcinoma and micropapillary carcinoma

Abstract: Aims Micropapillary variant of mucinous carcinoma of the breast (MPMC) is a rare histological form of oestrogen receptor (ER)‐positive invasive carcinoma that is characterised by micropapillary clusters of tumour cells in lakes of extracellular mucin. The aims of this study were to determine the genetic alterations underpinning MPMCs, and to determine whether they overlap with those of mucinous carcinomas and/or invasive micropapillary carcinomas. Methods and results DNA from five MPMCs was subjected to whole‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In our analysis, the global average and the hot spot analysis of sTILs and their spatial distribution, TLS and the patterns of distribution of TAPC were similar between pure and non-pure IMPC. However, a recent study based on array comparative genomic hybridization technology revealed no significant differences in the structural genomic profile and immunophenotype of mixed cases as compared to those of pure IMPCs [31,32]. The implementation of more detailed molecular analysis at single cell level together with the integration of spatial information may be useful to better understand biologic differences between pure and non-pure IMPCs [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the global average and the hot spot analysis of sTILs and their spatial distribution, TLS and the patterns of distribution of TAPC were similar between pure and non-pure IMPC. However, a recent study based on array comparative genomic hybridization technology revealed no significant differences in the structural genomic profile and immunophenotype of mixed cases as compared to those of pure IMPCs [31,32]. The implementation of more detailed molecular analysis at single cell level together with the integration of spatial information may be useful to better understand biologic differences between pure and non-pure IMPCs [33].…”
Section: Discussionmentioning
confidence: 99%
“…MUMPC consists of micropapillary clusters of tumor cells with scalloped edges floating in stromal mucin (10). Compared with PMBC, MUMPC has a higher rate of lymph node metastasis and an outcome intermediate between that of mucinous carcinoma and micropapillary carcinoma (MPC) (11). MUMPC was described as a micropapillary variant of PMBC by Ng in 2002 (12).…”
Section: Discussionmentioning
confidence: 99%
“…All cases were mixed tumors with a nonmucinous ductal component, except 1 tumor with features of ''micropapillary variant of mucinous carcinoma,'' a morphologic subtype with higher histologic grade and greater rates of lymphovascular invasion and lymph node positivity than pure mucinous carcinoma. [30][31][32][33] Published studies of this variant show the majority to be ER and PR positive, with up to 20% showing HER2 overexpression, although the rate of ''triplepositivity'' is not specifically indicated in these reports. Three tumors in our series displayed lobular differentiation, confirmed by lack of E-cadherin expression, including 2 pleomorphic invasive lobular carcinomas and 1 classic-type invasive lobular carcinoma.…”
Section: Discussionmentioning
confidence: 91%